2022
DOI: 10.3390/cancers14174245
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aryl Hydrocarbon Receptor (AhR) Expression Disrupts Cell Proliferation and Alters Energy Metabolism and Fatty Acid Synthesis in Colon Cancer Cells

Abstract: The aryl hydrocarbon receptor (AhR) plays a wide range of physiological roles in cellular processes such as proliferation, migration or control of immune responses. Several studies have also indicated that AhR might contribute to the regulation of energy balance or cellular metabolism. We observed that the AhR is upregulated in tumor epithelial cells derived from colon cancer patients. Using wild-type and the corresponding AhR knockout (AhR KO) variants of human colon cancer cell lines HCT116 and HT-29, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Previous studies have linked directly or indirectly AHR with CD44 signaling associated with cancer cell proliferation, migration and invasion [17][18][19][20]. In fact, many studies have shown that AHR can promote cell growth and survival of various tumor cells.…”
Section: -Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have linked directly or indirectly AHR with CD44 signaling associated with cancer cell proliferation, migration and invasion [17][18][19][20]. In fact, many studies have shown that AHR can promote cell growth and survival of various tumor cells.…”
Section: -Discussionmentioning
confidence: 99%
“…In fact, many studies have shown that AHR can promote cell growth and survival of various tumor cells. AHR knockout cells showed a decreased proliferation rate, accompanied by altered cell cycle progression [20]. Loss of AHR was linked to inhibition of the expression and/or activity of the components of the PI3K/Akt signaling pathway [20].…”
Section: -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of AhR enhances the invasive capacity of the MDA-MB-231 breast cancer cells, but on the contrary decreases cell proliferation and proliferation-related genes [ 70 ]. Furthermore, deletion of AhR in the colon cancer cells HCT116 and HT29 represses proliferation in a cell-specific manner [ 71 ]. This was concomitant with altered cell cycle progression, decreased ATP production, suppression of fatty acids biosynthetic pathway, and reduced expression and/or activity of the components of the PI3K/AKT pathway [ 71 ].…”
Section: Role Of Ahr In Cancer At Glancementioning
confidence: 99%